Establishing the Exposure‐QT Relationship During Bedaquiline Treatment Using a Time‐Varying Tuberculosis‐Specific Correction Factor (QTcTBT) - Thanakorn Vongjarudech; Anne‐Gaëlle Dosne; Bart Remmerie; Mats O. Karlsson; Elin M. Svensson (CPT: Pharmacometrics & Systems Pharmacology, 2025)
ABSTRACT Evaluating QT prolongation induced by anti‐tuberculosis (TB) drugs in patients with active TB, who often experience tachycardia, is challenging due to the limitations of Fridericia's correction factor (QTcF) in decorrelating QTc from heart rate (HR). Previous exposure‐QTcF analyses in patients with active TB were able to alleviate the limitation of QTcF but required advanced model‐based methodologies, incorporating a non‐drug‐related, “secular” trend in the model to dissociate drug and non‐drug‐related effects on QT. Recently, we developed and validated a time‐varying QT correction method (QTcTBT) that more accurately accounts for the HR changes during TB treatment. In the present work, using data from 429 patients with multidrug‐resistant TB across two Phase IIb trials, we re‐evaluated the exposure‐QTc relationship for bedaquiline by applying QTcTBT instead of QTcF. Our analysis showed that when HR changes were accounted for using QTcTBT, a typical maximum M2 (bedaquiline metabolite) concentration (326 ng/mL, mean maximal concentration (Cmax) at the end of 2‐week loading phase) was associated with a 7 ms QTc interval prolongation (90% CI: 5.9–8.2). This estimate closely aligns with the previously reported M2 effect of 7.9 ms (90% CI: 6.8–9.3), derived from the exposure‐QTcF model. The consistency between the two methodologies further supports the use of QTcTBT for estimating the QTc prolongation effects of anti‐TB drugs.